PENGARUH PENGGUNAAN MAKE A MATCH TERHADAP PEROLEHAN BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Ferdiana Putri, Reza Pricilla; Marzuki, Marzuki; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis problem of this research is ?How the influence of using make a match type to the acquisition of civic educations learning in state primary school 55 western Pontianak??. This study aims to determine the effect of using make a match type on the aqcuistion of civic educations learning in public primary school 55 western Pontianak. The research method used is experimental method. The from of research used is quasi experimental design, by experimental design nonequivalent control group design. Population in this research is all students of class IV of state primary school 55 Western Pontianak that is amounted to 63 learners. The sample in this study were students of class IV A which amounted to  32 people and students of class IV B which amounted to 31 people. Data collection techniques used are measurement techniques. And the data collection tool used is an objective test of 40 questions. Based on hypothesis test result two path anava obtained Fcount  amount 9,454 and Ftable (? 5 %) amount 3,99. Which mean Fcount (9,454) > Ftable (3,99), then Ha be accepted. So it can be concluded that there is influence the use of make a match type to the acquistions of learning citizenship education in elementary school in western Pontianak. From result of means the type of make a match gives a moderate effect. On the acquistion of civic educations learning in the western primary school of western Pontianak. Keywords:  Technique, Make a Match, Acquisition of Civic Education Learning